Emerging PD-1/PD-L1 targeting immunotherapy in non-small cell lung cancer: Current status and future perspective in Japan, US, EU, and China - Mizuno, Takaaki; Katsuya, Yuki; Sato, Jun; Koyama, Takafumi; Shimizu, Toshio; Yamamoto, Noboru (Frontiers in Oncology, 2022)
Non-small cell lung cancer (NSCLC), one of the deadliest types of cancers worldwide, has been the target of immunotherapy due to its high immune antigenicity. With the addition of immune-checkpoint inhibitors (ICIs), including anti-PD-1/PD-L1 antibodies, as an indispensable and powerful regimen for the treatment of this lethal disease, the median survival time for patients with stage IV NSCLC is approximately 2 years. In contrast, the response rate to ICIs remains less than 50%, even if the patients are selected using biomarkers such as PD-L1. Pharmaceutical companies have begun to develop additional anti-PD-1/PD-L1 antibodies to overcome resistance and are devising further immunotherapy combinations. More than 20 anti-PD-1/PD-L1antibodies have been approved or are currently in development. Numerous combination therapies are under development, and several combination therapies have provided positive results in randomized controlled trials. This review aimed to examine the current status of approved and investigational anti-PD-1/PD-L1antibodies for NSCLC in Japan, the United States, the European Union, and China. Further, this review discusses the challenges and future perspectives for developing new ICIs in alignment with the global developments in Japan.